Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together (NHT) Terhadap Hasil Belajar IPA Ditinjau Dari Keterampilan Proses Sains - Rima Agustina; Asep Setiadi; Andry Fitrian (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
The study was entitled the effect of NHT (Numbered Head Together) Cooperative Learning Methods on Science Learning Outcomes in terms of Learning Process Skills (Experiments in Class VIII Students of Mts. Al-Falah Harapan Jaya Cibinong Bogor). The experimental method is to provide different types of treatment to two different types of treatment. student study groups. One group was used as an experimental group, namely given the physics learning treatment with the (Numbered Head Together) method, while the other group as a control group with the physics learning treatment using conventional methods. The research design used was post-test (Control Design Group). With the results of the study: 1. The Effect of the Interaction of the Use of Learning Methods (Numbered Head Together) (NHT) on Science Learning Outcomes in terms of Student Learning Process Skills in Human Motion System Material, it can be concluded that there is no significant influence between the use of the method. defender jaran (Numbered Head Together) (NHT) on science learning outcomes in terms of student learning process skills; 2. The Influence of the Use of Learning Methods (Numbered Head Together) (NHT) on Science Learning Outcomes in Human Movement System Material, it can be concluded that there is a significant influence between the use of the learning method (Numbered Head Together) (NHT) on the science learning outcomes; 3. The Influence of Student Learning Process Skills on Science Learning Outcomes in Human Motion System Material it can be concluded that there is a significant influence between student learning process skills on science learning outcomes.